Searching for eV-scale sterile neutrinos with eight years of atmospheric neutrinos at the IceCube Neutrino Telescope - Aartsen, MG; Abbasi, R; Ackermann, M; Sarkar, S; Adams, J; Aguilar, JA; Ahlers, M; Ahrens, M; Alispach, C; Amin, NM; Andeen, K; Anderson, T; et al. (American Physical Society, 2020)
We report in detail on searches for eV-scale sterile neutrinos, in the context of a 3+1 model, using eight years of data from the IceCube neutrino telescope. By analyzing the reconstructed energies and zenith angles of 305,735 atmospheric $ν_μ$ and $\bar{ν}_μ$ events we construct confidence intervals in two analysis spaces: $\sin^2 (2θ_{24})$ vs. $Δ m^2_{41}$ under the conservative assumption $θ_{34}=0$; and $\sin^2(2θ_{24})$ vs. $\sin^2 (2θ_{34})$ given sufficiently large $Δ m^2_{41}$ that fast oscillation features are unresolvable. Detailed discussions of the event selection, systematic uncertainties, and fitting procedures are presented. No strong evidence for sterile neutrinos is found, and the best-fit likelihood is consistent with the no sterile neutrino hypothesis with a p-value of 8% in the first analysis space and 19% in the second.